2017
DOI: 10.3892/mmr.2017.7594
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid alleviates diabetic rat carotid artery injury through the inhibition of NLRP3 inflammasome signaling pathways

Abstract: The overexpression of inflammasome components is correlated with diabetes‑associated complications. Oleanolic acid is a triterpenoid compound which is important in arterial injury. The present study evaluated whether oleanolic acid improved diabetic rat carotid artery injury through the inhibition of nucleotide‑binding domain, leucine‑rich‑containing family, pyrin domain‑containing‑3 (NLRP3) inflammasomes signaling pathways. A diabetic rat model was induced using streptozotocin (60 mg/kg) and underwent carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…Importantly, we demonstrated that in human placental tissues, OleaVita notably inhibited the activation of NLRP3 inflammasomes, resulting in a decrease in the secretion of mature IL-1β. Consistent with our present results, An et al [31] and Kim et al [19] reported that oleanolic acid attenuated carotid artery and pulmonary injuries through the inhibition of NLRP3 inflammasomes using in vivo experimental models. Recently, NLRP3 inflammasome activation has been shown to be involved in various pregnancy complications, such as preeclampsia, spontaneous preterm labor, and hypertension in pregnancy [9,14].…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, we demonstrated that in human placental tissues, OleaVita notably inhibited the activation of NLRP3 inflammasomes, resulting in a decrease in the secretion of mature IL-1β. Consistent with our present results, An et al [31] and Kim et al [19] reported that oleanolic acid attenuated carotid artery and pulmonary injuries through the inhibition of NLRP3 inflammasomes using in vivo experimental models. Recently, NLRP3 inflammasome activation has been shown to be involved in various pregnancy complications, such as preeclampsia, spontaneous preterm labor, and hypertension in pregnancy [9,14].…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, according to the literature, OA improves beta-cell function through increasing insulin biosynthesis and secretion and also improves glucose tolerance [10]. This idea coincides with different studies included in our review that reported improvements of glucose tolerance both in glucose [35,36,38,39,40,42,46] and in insulin [35,42] tolerance tests, as well as reductions of FBG [30,35,38,42,43,44].…”
Section: Discussionsupporting
confidence: 89%
“…Another possible hypotensive mechanism of action of OA could be the increase of the production of nitric oxide (NO), a vasodilator factor that is diminished in endothelial disfunction induced by cardiovascular risk factors such as hypertension, obesity, diabetes, and dyslipidemia [15]. This is in agreement with the increase of serum NO levels produced by the action of OA reported by Bachhav et al [28], Jiang et al [32], and An et al [44]. However, Wang et al [43] reported the opposite, which might be explained by the fact that they studied rats [43] fed with a high fat and fructose diet.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations